Bleiberecht in der Gastro-Küche Migrationspolitische Regulierungen und Arbeitsverhältnisse von Geflüchteten mit unsicherem Aufenthaltsstatus - Kalbermatter, Jacqueline (Differenzen, 2020)
Right to stay in the gastro-kitchen Migration policy regulations and working conditions of refugees with precarious residence permit status Asylum policy is labour market policy. Yet, the demarcation lines in migration policy between "refugees" and "labour migrants" fail to take this fact into account. It is therefore hardly surprising that this connection remains obscure both in the context of migration policy as well as in the research landscape. In contrast, this book focuses on the interactions between migration policy regulations and the working conditions of refugees with precarious residence permit status. For a start, that means opening the analytical view in the field of asylum policy negotiations to the dynamics of everyday struggles for rights and social participation in the case of Swiss gastronomic companies. Jacqueline Kalbermatter examines how social differentiations become apparent in the kitchen and in the labour process, and asks about their specific relation to the residence permit status and geographical origin of the workers. In the end, the conception of gastronomic companies as a place of ongoing negotiation processes of entrepreneurs and workers allows for a new perspective to be adopted. It reveals the entanglements and ambivalences between asylum policy and the regulation of labour force problems, which otherwise remain hidden.